Knowledge sharing talk by Securities Commission Malaysia - Hasli, Anita (UiTM Sarawak, 2016)
BBA (Hons) Finance organized the first session of a yearly held series of talks by Securities Commission Malaysia for the students and academic staff of BBA (Hons) Finance. The event was officiated by Madam Norzaihan Hashim, Ketua Pusat Pengajian, Faculty of Business Management. 154 students together with the academic staff of BBA (Hons) Finance attended the presentation by En. Rohaimi Mohamad, Senior Manager, Investor Affairs & Complaints Department Securities Commission. The first part of the presentation covered the roles and responsibilities of the Securities Commission while the second part of the presentation covered investor education, investment products and scams. After the presentation session, a discussion between the academic staff of BBA (Hons) Finance and En. Rohaimi Mohamad was held. Among the important topics discussed were potential students' activities in the form of workshops and education camps. A memorandum of understanding is in the pipeline to ensure continuous sharing of knowledge and information between the Faculty of Business Management, UiTM Sarawak Campus and Securities Commission Malaysia.